THE RELATIONSHIP BETWEEN FUTURE TIME PERSPECTIVE AND CAREER DECISION MAKING SELF-EFFICACY - Enstin, Nur; Japar, Muhammad; Sunawan, Sunawan (Study Program of Guidance and Counseling, Postgraduate Program, Universitas Negeri Semarang, 2020)
Career decision making self-efficacy is needed by adolescences to accomplish tasks in career decision making. Individuals with high career decision making self-efficacy would be successful in making the right decision for themselves. This study aimed at proving the effect of future time perspective on career decision making self-efficacy seen from every aspect. The study used correlational design, and involved 120 subjects selected using purposive sampling. To collect the data, the researchers utilized the short form of career decision self-efficacy, and future time perspective. The results of linear regression analysis showed that the overall effects of the future time perspective aspects on self-appraisal was (R = 0.437; F = 9,150; p = <0.05), the future time perspective perspective on the goal selection was (R = 0.257; F = 2.740; p = <0.05), and the future time perspective aspects on planning for the future was (R = 0.458; F = 10,247; p = <0.05). However, there found no significant relationship between the whole aspects of future time perspective on occupational information, and problem solving. Further, the implications of the findings are discussed in this article.